Efecto del biol en el crecimiento de plántulas de cacao, Theobroma cacao L. Distrito de San Juan de Bigote, Morropón - Piura - Torres Chaname, Merary Ithamar (2025)
The cultivation of Cocoa Theobroma cacao L has become an important source of income for some Peruvian communities, the growth of this crop generates a greater demand for organic fertilizers for agro-industrial production and small-scale agriculture, the use of liquid organic fertilizers such as biol has increased, by providing a solution to the fertility problem, producing good quality seedlings and increasing their fertility. The general objective of this research was to evaluate the effect of biol on the growth of cocoa seedlings Theobroma cacao L in the nursery stage in the district of San Juan de Bigote, Morropón-Piura, having 3 treatments, T1 (Control), T2 (Biol), T3 (Compost), the measurements were made biweekly in the period of 90 days, to determine the growth the length and diameter of the stem, number and length of leaves were measured. The results obtained showed statistically significant differences between treatments, leading to the following conclusions: 1) Biol has a positive effect on the growth of nursery stage cocoa seedlings, showing higher values ​​in stem length and diameter, length and number of leaves, having statistically significant differences with respect to the control, 2) The effect of biol on the growth of cocoa seedlings is greater than T3 (compost) having a statistically significant difference for all.